The Effect Emotional Intelligence And Organizational Commitment Of Front Office Nurse Employees The Effectiveness Care Delivery - Natalia Christy Tarigan, Chindy; Perizade, Badia; Isnurhadi, Isnurhadi; Yusuf, Muhammad (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to see how the quality of services is influenced by factors of emotional intelligence and organizational commitment in providing services at Siloam Sriwijaya hospital, emotional intelligence is a person's ability to regulate their emotional life with intelligence, and Organizational Commitment is a situation where an individual takes sides with the organization and his goals and desires . The population studied in this study is the kariawan of Siloam Swiwijaya Hospital who perform direct services to hospital patients. This study used multiple regression analysis by adding the tt test and the F test. From the results of the respondent data analysts obtained were